Importance of national health authority regulation for control of public health problems - Robles-Guerrero, Luis Ricardo (2011)
By means of the State countries officially approach the topic of Public Health. The National Health Authority (NHA) is responsible for ensuring public asset in health matters including confronting Public Health problems (PHP) as it holds exclusive stewardship of regulation and supervision functions. Norm emission is expression of this function and objectives of NHA activity includes control and solution of Public Health problems. According to PHP causes norms emitted will be oriented to respond what to do, how should it be, or how to do it? Norm emission obeys to the principles of obligatory fulfillment, national implementation, technical and scientific basis, operative viability, accordance with reality, defense of Public Health goods, and sanitary political coherence. Exercise of NHA regulation and supervision function will be efficient when PHP are solved thus contributing to improving population health, fundamental reason of its existence.